PENGARUH ADIKSI GAME ONLINE TERHADAP KOMUNIKASI INTERPERSONAL DAN MOTIVASI BELAJAR PADA SISWA DI SMKN 5 BANJARMASIN - Andriana, Riya; Handayani, Eka Sri; Hayati, Sri Ayatina (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2024)
This study aims to determine whether online gaming addiction influences interpersonal communication and learning motivation among students at SMKN 5 Banjarmasin. The research employs a quantitative method with a correlational design. The population consists of 184 students, with purposive sampling specifically targeting those experiencing online gaming addiction, resulting in a sample of 42 students. The research instruments include questionnaires covering online gaming addiction, interpersonal communication, and learning motivation. Instrument validity was tested using two methods: expert validity and construct validity. The reliability of the instruments was measured using the Cronbach's Alpha coefficient. Data analysis was conducted using MANOVA. The results showed that online gaming addiction did not significantly affect interpersonal communication (significance value 0.103 > 0.05) but had a significant effect on learning motivation (significance value 0.027 < 0.05). Furthermore, no significant effect was found on both interpersonal communication and learning motivation simultaneously (most significance values > 0.05). The study concludes that online gaming addiction only affects learning motivation, while it does not impact interpersonal communication or the combination of both. The implications suggest that interventions to reduce the impact of online gaming addiction at SMKN 5 Banjarmasin should focus on improving learning motivation. Additionally, further research is needed to understand the dynamics between online gaming addiction and other aspects of student development.